KAJIAN KELAIAKAN BANGUNAN GEDUNG SMP AL FATTAH BOYOLALI LINGKUP ARSITEKTUR DAN STRUKTUR - Dody Irnawan; Mohammad Paesal Tantowi (Kodepena (Komunitas Dosen Penulis dan Peneliti Indonesia), 2022)
Buildings are places for humans to carry out various activities. Buildings also have a very important role in character formation, embodiment of productivity, and identity. In addition, the building also functions as a place for humans to carry out their activities, whether for daily or residential, religious, business, socio-cultural or special activities. In general, the inspection of the feasibility of the building is carried out by means of visual observation of the physical condition of the building on the components of Architecture, Structure and Test using tools. Based on the results of field observations for Technical Architecture which includes aspects of comfort, health, safety and structure, the AL-Fattah Junior High School building has fulfilled all the assessment points and it can be concluded that the Al-Fattah Junior High School building has met and is recommended to get a Function-worthy